Impact of Islamic Work Ethics on Organizational Citizenship Behaviors and Knowledge-Sharing Behaviors - Murtaza, Ghulam (Journal of business ethics, 2016)
This study examines the impact of Islamic Work Ethic (IWE) on organizational citizenship behaviors (OCBs) and knowledge-sharing behaviors (KSBs) among university employees in Pakistan. A total of 215 respondents from public sector educational institutions participated in this research. The findings suggest that IWE has a positive effect on OCBs. In other words, individuals with high IWE demonstrate more citizenship behaviors than those with low IWE. The findings also suggest a positive effect of IWE on KSBs. Individuals with high IWE exhibit more KSBs than those with low IWE. The paper also discusses the theoretical and practical implications of these findings.